Prevalence and risk factors of acute kidney injury in polytrauma patients at Muhimbili Orthopedic Institute, Tanzania - Muhamedhussein, Mohamed S. (Afr J Emerg Med, 2021)
BACKGROUND: Polytrauma can lead to multi-organ dysfunction in addition to the local injuries. Acute kidney injury (AKI) is one of the most common causes and contributors to the high morbidity and mortality. Prevalence of acute kidney injury in trauma patients is as reported to be as high as 40.3%. Early detection and management leads to better outcomes. The prevalence of AKI among polytrauma patients remains unknown in our setting. METHODOLOGY: A cross-sectional study involving all adults with polytrauma who presented at the emergency department at Muhimbili Orthopedic Institute (MOI) was designed. A score of ≥18 on the New Injury Severity Score (NISS) screening tool was used to identify polytrauma patients. The Kidney Disease Improving Global Outcomes (KDIGO) criteria was used to identify patient with polytrauma who developed acute kidney injury. Descriptive statistics were then obtained followed by hypothesis testing between variables with the chi squared test. Logistic regression models were used to determine factors associated with acute kidney injury. RESULTS: More than half (56.4%) of the patients were between 26 and 40 years and 92.3% of the polytrauma patients were males. Almost 2/5th (38.5%) of the polytrauma patients had acute kidney injury – half of these had stage 1 AKI, 33.3% had stage 2 AKI and the remaining 16.7% had stage 3 AKI. On multivariate logistic regression, it was found that patients who were older than 45 years (OR 8.53, CI 1.65–43.89, p = 0.01) and those patients with Systemic Inflammatory Response Syndrome (SIRS) (OR 21.83, CI 1.66–286.2, p = 0.019) had higher risk of acute kidney injury. CONCLUSION: There is high prevalence of AKI among polytrauma patients. Elderly patients and those with SIRS were seen to have higher likelihood of AKI.